(untitled) (Ustozlar uchun, 2025)
Corpus linguistics has emerged as a powerful methodology for studying language empirically. Its establishment as a field highlights the importance of large-scale, structured language data in understanding linguistic patterns, usage, and variation. The evaluation of corpus linguistics demonstrates its contributions to lexicography, language teaching, translation studies, and natural language processing, while also acknowledging its limitations and challenges.